Risk assessment of chemicals : (Kluwer Academic Publishers, 1995)
The risk management of chemicals represents an international challenge. It occupied a prominent place on Agenda 21 of the UN Conference on Environment and Development (UNCED), held in Rio de Janeiro in 1992. The development and harmonization of risk assessment methods are a necessary prerequisite to successful risk management. The book provides an introduction to the risk management of chemicals. It contains basic background information on sources and emissions, distribution and fate processes, toxicology and ecotoxicology and estimation methodologies. It describes basic principles and methodologies for hazard and risk assessment of chemicals in the context of the legislative framework. This Introduction contains essential information for students of the environmental sciences and for those professionally involved in the rapidly developing field of risk assessment and management of chemicals. It also supports the Uniform System for the Evaluation of Substances (USES), a computerized risk assessment system.